Steel Structure Analysis of Workshop Facility in PT Pamapersada Nusantara - Halim, Mirza Abdul; Rutama, Dedy; Sari, Ribut Nawang (Journal of Global Engineering Research and Science, 2022)
Structural planning in every building construction, aims to take into account the ability to withstand the loads that occur. The structural elements must be designed and calculated based on the appropriate combination of standard loads. Workshop facility project at PT. Pamapersada Nusantara uses a steel structure with steel profiles for columns and beams. The function of the steel profile as a cross section of the structure is very important, for that it is necessary to analyse and design the right steel profile for the structural elements of steel columns and beams at the Workshop Facility Project of PT. Pamapersada Nusantara. The method used in this research is based on a case study on the object of research in the project. This building structure planning was analysed using a computer-based structural calculation program, namely the SAP2000 v.22 program, referring to SNI 1729-2020 concerning Procedures for Planning Steel Structures for Buildings and SNI 1726:2019 Procedures for Planning Earthquake Resistance for Building Structures and Non-Building and SNI 1727:2020 Minimum Load for Design of Buildings and Other Structures and Indonesian Loading Regulations for Buildings (PPIUG 2019). The result of structure analysis using SAP2000 V.22, indicates that there are no failed frames/structures with structural susceptibility > 1.0 (red) meaning that they are unable to carry the load that will occur. Meanwhile, frames/structures < 1.0 (grey, blue, green, yellow, orange) mean that they are capable of bear the brunt of what is to come.